Conocimientos, actitudes y prácticas sobre el virus del papiloma humano en personas privadas de libertad pabellón femenino del Centro de Rehabilitación Social de Loja - Ocampo Ortega, Hipatia Annabel (2015)
In the etiology of cervical cancer, the Human Papilloma Virus today is accepted your participation like the considerable increase of incidence. The importance of this problem was considered for the following investigation which search to determine the relation ship between the level of knowledge about HPV with attitudes and practices regarding this infection in said group; to know if the women deprived of liberty of the social rehabilitation center of Loja have knowledge about HPV; to evaluate the level knowledge about HPV in the group study; to identify who attitudes show the prisioners in front of the HPV; to establish what specific practices make for the prevention prevention and monitoring of HPV infection; to contribute improve the knowlegde and prevention of HPV infection in the study group, by talks and instructional triptych about of subject. This investigation is descriptive, prospective, transversal, applied to 15 women deprived of liberty in the Social Rehabilitation Center of Loja. The information was collected through a personal survey, demonstrating that most people do not know about the virus, and those which know about it, mostly have a low level of knowledge. However, those who have a high knowledge and one worried attitude perform predisposing practices for acquiring the infection. The conclusion is that there is no coherent relationship between, the level of knowledge, and attitudes with preventive practices in the study group. Therefore this investigation serves as a source of information about the topic, to achieve a greater interest in creating prevention programs and to reduce the incidence numbers of Human Papilloma Virus infection and cervical cancer. Key words: Knowledge, Attitudes, Practices, Human Papilloma Virus; Persons Deprived of Liberty.